Understanding the antecedents and consequences of sustainable competitive advantage: Testing intellectual capital and organizational performance - Partiwi Dwi Astuti; Luh Kade Datrini; Anis Chariri (Economies, 2023)
This study aimed to investigate the relationship between intellectual capital (human capital, relational capital, and structural capital) and sustainable competitive advantage, and the relationship between sustainable competitive advantage and organizational performance. The sample used was 308 SMEs located in Denpasar, Bali Province, Indonesia. Data were collected using a questionnaire that was sent directly to the CEO of the SMEs. Data were analyzed using SEM-PLS with WarpPLS 8.0. The findings show that there is a significant positive relationship between each dimension of intellectual capital (human capital, relational capital, and structural capital) and sustainable competitive advantage. Sustainable competitive advantage is also significantly and positively related to organizational performance. This study contributes to the understanding of intellectual capital in the value creation process of SMEs in developing countries. This study also enriches the previously developed conceptualization of intellectual capital by proposing intellectual capital as an important variable underlying the sustainability practices of companies, which allows them to achieve superior performances.
Keywords: 330; intellectual capital; sustainable competitive advantage; organizational performance